Accumulation of intestinal tissue 3-deoxyglucosone attenuated GLP-1 secretion and its insulinotropic effect in rats. Issue 1 (December 2016) - Zhang, Lurong; Song, Xiudao; Zhou, Liang; Liang, Guoqiang; Xu, Heng; Wang, Fei; Huang, Fei; Jiang, Guorong
Abstract Background Our recent findings support the idea that 3-deoxyglucosone (3DG), a dietary composition, has been suggested as an independent factor for the development of prediabetes. Secretion of glucagon-like peptide-1 (GLP-1) has been suggested to be impaired in T2DM and in conditions associated with hyperglycemia. Since low oral bioavailability of 3DG has been indicated in a single administration study, in the present study we examined if 3DG is capable of accumulating in intestinal tissue of rats after 2-week administration of 3DG, and the 3DG treatment affects GLP-1 secretion and glucose tolerance. Methods Rats were administered by gastric gavage for 2 weeks. We measured 3DG contents of intestinal tissues (by HPLC), plasma levels of total GLP-1 (by ELISA), insulin and glucagon (both by radioimmunoassay) and blood glucose concentrations. The expressions of the sweet receptor subunits (TAS1R2, TAS1R3) and its downstream molecule TRPM5 in duodenum and colon tissues of rats were quantified by WB. We examined GLP-1 secretion in enteroendocrine STC-1 cells exposured to 3DG. Results 3DG treatment for 2 weeks increased 3DG content of intestinal tissues, fasting blood glucose concentration, and reduced plasma concentrations of GLP-1 and insulin at fasting and 15 and 180 min after the glucose load and oral glucose tolerance in conjunction with increased plasma glucagon concentrations. The expressions of TAS1R2, TAS1R3 and TRPM5 were shown to be reduced whereas 3DG treatment did not affect plasma dipeptidyl peptidase-4 activity, indicating an impaired GLP-1 secretion in 3DG-treated rats. This idea was further supported by the fact that exposure to 3DG directly decrease GLP-1 secretion in STC-1. Conclusion It is the first demonstration that 3DG was capable of accumulating in intestinal tissue and thereby decreased secretion of GLP-1 and insulin in a similar manner. 3DG-treated rats developed impaired glucose regulation (IGR) with obviously pancreatic islet cell dysfunction. It is further concluded that a decrease in the biological function of GLP-1 resulting from the decreased GLP-1 secretion is the most likely mechanism for the impaired insulin secretion, which ultimately promoted the development of IGR. These results will also contribute to a better understanding of the significance for restoring physiological GLP-1 secretion.